Legal standing in cases of securitization of mortgage loan.: Comment on the Castellon Provincial Court´s Order dated 19th October 2017 (Acta Judicial Journal, 2018)
The referred Court Order addresses the problem of legal standing of the plaintiff on foreclosure, when the mortgage loan that is executed was already securitised The order stablish that by means of the securitization the assignment of receivable takes place, so the rightholder  start to be the securitization fund. The fund owner of the mortgage loan, prior to the exercise of the mortgage action must have the registration of title in the Land Registry,  especially when  after 2015 law reforms it is possible this type of registration.
Keywords: Credit Securitization; foreclosure; active legitimation; mortgage loan guaranteed; mortgage market; Land Registry.